2015
DOI: 10.1097/mao.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Outcomes of Wait-and-Scan and the Role of Radiotherapy in the Management of Vestibular Schwannomas

Abstract: The wait-and-scan modality is ideal for management of VSs in the elderly population and also in younger patients with intrameatal tumors. Considering the fact that a large percentage of tumors do not require any form of treatment, the role of RT in VSs needs to be reinvestigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…In principle, it was the natural history of AN that dictated our treatment approach: most small tumours do not grow, but hearing function declines inexorably regardless of tumour growth. The wait-and-see policy is justified by the finding of no tumour growth for a considerable proportion of small tumours 1 2 4 5 18 despite progression of hearing loss. Follow-up seems to be the most predictable variable when assessing hearing outcome – whatever the therapeutic approach – because hearing decline is inescapable when tumours are observed over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, it was the natural history of AN that dictated our treatment approach: most small tumours do not grow, but hearing function declines inexorably regardless of tumour growth. The wait-and-see policy is justified by the finding of no tumour growth for a considerable proportion of small tumours 1 2 4 5 18 despite progression of hearing loss. Follow-up seems to be the most predictable variable when assessing hearing outcome – whatever the therapeutic approach – because hearing decline is inescapable when tumours are observed over a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of growth after 5 years of follow-up ranges from 0 3 to 7%, 8 with some recent studies having demonstrated tumor growth after many years of follow-up. [9][10][11][12] These studies recommend continuing a lifelong policy of surveillance imaging, albeit at a reduced interval frequency for stable tumors. However, these papers have not specifically focused on the older patient age group, and our data suggest that a policy of discontinuation of imaging surveillance after 5 years tumor stability can be considered in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reported intraoperative complications and resulting postoperative morbidity, in most cases a wait-and-scan policy is adopted for VS. 17 However, an alternative includes radiosurgical management of VS. Adequate control of VS by radiosurgery has been documented.…”
Section: Discussionmentioning
confidence: 99%